Pharmacological Profile of the Sodium Current in Human Stem Cell-Derived Cardiomyocytes Compares to Heterologous Nav1.5+β1 Model - Van de Sande, Dieter V.; Kopljar, Ivan; Teisman, Ard; Gallacher, David J.; Snyders, Dirk J.; Lu, Hua Rong; Labro, Alain J. (Frontiers in Pharmacology, 2019)
The cardiac Nav1.5 mediated sodium current (INa) generates the upstroke of the action potential in atrial and ventricular myocytes. Drugs that modulate this current can therefore be anti- or pro-arrhythmic, which requires preclinical evaluation of their potential drug-induced inhibition or modulation of Nav1.5. Since Nav1.5 assembles with, and is modulated by, the auxiliary β1-subunit, this subunit can also affect the channel´s pharmacological response. To investigate this, the effect of known Nav1.5 inhibitors was compared between COS-7 cells expressing Nav1.5 or Nav1.5+β1 using whole-cell voltage clamp experiments. For the open state class Ia blockers ajmaline and quinidine, and class Ic drug flecainide, the affinity did not differ between both models. For class Ib drugs phenytoin and lidocaine, which are inactivated state blockers, the affinity decreased more than a twofold when β1 was present. Thus, β1 did not influence the affinity for the class Ia and Ic compounds but it did so for the class Ib drugs. Human stem cell-derived cardiomyocytes (hSC-CMs) are a promising translational cell source for in vitro models, that express a representative repertoire of channels and auxiliary proteins, including β1. Therefore, we subsequently evaluated the same drugs for their response on the INa in hSC-CMs. Consequently, it was expected and confirmed that the drug response of INa in hSC-CMs compares best to INa expressed by Nav1.5+β1.